ACCOUNTING IN LOCAL WISDOM: REVEALING BARTER TRADITION IN WULANDONI NUSA TENGGARA TIMUR - Marselina, Apriana (Program Studi Sosiologi Universitas Malikussaleh, 2025)
This study aims to find out two things: first, to understand more deeply about the exchange rate of goods in the barter tradition in Wulandoni District, Lembata Regency, East Nusa Tenggara, and second, to analyze the factors that affect the existence of the barter market in the midst of the circulation of banknotes in the modern century. The type of research used is qualitative descriptive research, which is carried out at the Wulandoni Barter Market. Data were obtained through observation, interviews, documentation, and literature studies. The results of the study show that in barter transactions in Wulandoni District, the exchange rate of goods is determined based on an agreement, without involving money as an intermediary. This barter system uses a traditional rule called